2013
DOI: 10.1111/iju.12284
|View full text |Cite
|
Sign up to set email alerts
|

Cystectomy and urinary diversion as management of treatment‐refractory benign disease: The impact of preoperative urological conditions on perioperative outcomes

Abstract: Abbreviations & AcronymsObjectives: To investigate perioperative outcomes associated with cystectomy and urinary diversion for treatment-refractory benign urological disease. Methods: A cohort of patients who underwent cystectomy for infection, fistula, bleeding, incontinence, neurogenic bladder or pain between January 2004 and June 2012 was established. Data included baseline demographics, indications for cystectomy and prior treatments, and complications at 30 and 90 days. Primary outcome measures were 30-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The increasing use of radiation therapy (XRT) for malignancies, including external beam radiation (EBRT) and brachytherapy, presents additional challenges in the management of treatment-refractory benign disease because of damage to the surrounding tissue including fibrosis and changes in vascularity. 6 Previous studies have focused on morbidity and complication rates for cystectomy and urinary diversion for benign disease 7,8 ; however, the impact of cystectomy and urinary diversion for radiation-induced treatmentrefractory benign disease on the functional and HRQOL outcomes has not been previously studied. Our objective was to evaluate the long-term quality of life in patients with nonmalignant treatment-refractory disease before and after cystectomy and urinary diversion and characterize the perioperative complications and functional outcomes in this unique population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing use of radiation therapy (XRT) for malignancies, including external beam radiation (EBRT) and brachytherapy, presents additional challenges in the management of treatment-refractory benign disease because of damage to the surrounding tissue including fibrosis and changes in vascularity. 6 Previous studies have focused on morbidity and complication rates for cystectomy and urinary diversion for benign disease 7,8 ; however, the impact of cystectomy and urinary diversion for radiation-induced treatmentrefractory benign disease on the functional and HRQOL outcomes has not been previously studied. Our objective was to evaluate the long-term quality of life in patients with nonmalignant treatment-refractory disease before and after cystectomy and urinary diversion and characterize the perioperative complications and functional outcomes in this unique population.…”
Section: Resultsmentioning
confidence: 99%
“…5,7,[18][19][20][21] Although the impact of disease and treatment has been previously studied for invasive UCB and radical cystectomy, 5,12,22,23 little is known about the effect of radiation-induced treatment-refractory disease on patients' HRQOL. This study identified significant impairments on the physical and mental health of these patients, especially in the role limitations due to physical and emotional problems (RH, RE), vitality (EF), and SF.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In series of cystectomy with urinary diversion for benign indications other than hemorrhagic cystitis, severe (Clavien III to V) complications have been reported in 6.4% to 46% of patients, with mortality rates between 0% and 4%. 11,12 Notably, a series of patients with cystitis secondary to cyclophosphamide by Stillwell and Benson included 5 patients who underwent cystectomy for hemorrhagic cystitis. 5 This report included patients across a wide age range (33 to 72), with perioperative mortality in 1 case.…”
Section: Discussionmentioning
confidence: 99%
“…1 All patients with radiation-induced fistula experienced complications within 30 days after the cystectomy, and half of them were Clavien grade III or more. At 90 days, 50% of the patients with radiation-induced fistula still had the preoperative problems, whereas 83% of the rest of the cohort experienced resolution.…”
mentioning
confidence: 98%